Nexus between conservation agriculture and remote sensing: A review - Lawrence, Mango; Nuthammachot, Narissara; Som-ard, Jaturong (Agriculture and Natural Resources, 2024)
Importance of the work: Remote sensing technologies can be effectively integrated into conservation agriculture practices to improve soil health, soil moisture and the sustainability of agricultural systems. Objectives: To compile, analyze, and synthesize information and knowledge on the application of remote sensing technologies for evaluating soil health and productivity of agricultural crops under conservation practices. Materials & Methods: A literature review of secondary data from journals and online reports was used to analyze the relationship between remote sensing and conservation agriculture. The benefits and challenges were reviewed of remote sensing technologies in agricultural management and the theoretical paradigms in conservation agriculture and environmental policy. Results: Remote sensing technologies have the ability to collect data over large areas in a timely and cost-effective manner and to detect soil health and soil moisture, which in turn, can prevent pest outbreaks and diseases, resulting in increased crop yields. Researchers can utilize satellite imagery analysis to identify soil moisture levels to help farmers understand water dynamics and make decisions on irrigation scheduling, crop selection and soil conservation practices. This approach has been useful to farmers for planning water availability, adjusting irrigation schedules and implementing conservation practices to improve crop resilience and sustainability. Main finding: Advances in remote sensing technology have resulted in more efficient and accurate methods for monitoring soil moisture and health. Increasing access to remote sensing data through open data initiatives has provided a wealth of benefits to the agricultural community.